POLITICS AMONG SPORTS: FC BARCELONA AS THE SHAPERS OF CATALAN IDENTITY - Habibilla, Akbar Fasya; Imtiyaz, Zahra Nasywa (UIN Sunan Gunung Djati, 2024)
The article explores how FC Barcelona has played a significant role in shaping Catalan identity on a global scale. Through the lens of the Transnational Advocacy Network framework, the research delves into the club's international influence and its impact on catalyzing awareness and recognition of Catalonia as a distinct cultural and political entity. The study investigates how FC Barcelona's global fan base, iconic players, and strategic branding efforts have contributed to projecting Catalonia's identity beyond Spain's borders. By examining the club's role as a transnational advocate for Catalan culture and aspirations, the article sheds light on the intricate interplay between football, identity, and transnational networks in shaping the perceptions of Catalonia in the global arena.Â Keywords: FC Barcelona, Catalan, Transnational Advocacy Networks, Politics of Identity